Financial inclusion and economic growth in Islamic middle-income countries / Muhammad Shazwan Naim Zainal - Zainal, Muhammad Shazwan Naim (2018)
Financial inclusion has been become a crucial part as it is part of the financial development towards economic growth. But, there a few past researches studied about the financial inclusion as a whole towards economic growth especially in Islamic countries. The main purpose of this study is to identify the relationship and also the impacts of the key factors of the financial inclusion and economic growth in Islamic middle-income countries within year 2010 until year 2014. Based on the past research, mostly mentioned that there is a significant relationship between the financial inclusion and economic growth in their studied covered. In other hand, there is a few research result proved different perspectives. In findings, we found that the bank branches, deposits and borrowings have a significant relationship towards the economic growth and with the bank branches give the most impacts toward the economic growth.